The link between effective human resource practices and employee engagement with perceived organizational support as mediation: A case from Indonesia - Tri Widarmanti; Arif Partono Prasetio; Romat Saragih (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
The goal of every company is increasing the productivity, revenue and give the value added to shareholders, employee engagement gives higher productivity, and as the asset of the company, employee reflects the organization performance. The goal of this study is to explore if perceived organizational support can mediate the link between human resource practice and employee engagement. The approach utilized was a causal descriptive quantitative research method; this study distributes 240 questionnaires for a different position in 4 companies in Bandung - Indonesia. Data was measured and explained using path analysis technique. The mind findings are HR practice tend to affect the EE, but this effect is explained by the mediating influence of POS to better EE. POS will help employee to become more engaged with the organization, so organization must pay attention when introducing the HR policies, this process will decide the level of support workers experience and the degree to which they will interact with the current organization. Keywords: